Monday

April 21, 2014

April 21, 2014

Posted by **Lucy** on Monday, October 27, 2008 at 8:20pm.

(2c-1)^3=4c^2-1

I did this already:

(2c-1)^3-(4c^2-1)=0

(2c-1)^3-(2c+1)(2c-1)=0

But I need help with the next steps... Thank you!

- Math -
**Reiny**, Monday, October 27, 2008 at 8:28pm(2c-1)^3-(2c+1)(2c-1)=0

good so far, now take out a common factor

(2c-1)[(2c-1)^2 - (2c+1)] = 0 expand and simplify to

(2c-1)(4c^2 - 6c) = 0

(2c-1)(c)(4c-6) = 0

c = 1/2 or c = 0 or c = 3/2

**Related Questions**

More Math To Check Please - 4c^2 - 12c + 9 This is what I got: (2c+3)(2c-3) *Is ...

math - 24b^4c^3 / 6b^2c A) 3b^2c^2 B) 4b^4c^2 C) 4b^3c^2 D) 4b^2c^2 E) 3b^4c^3

Math - Simplify each rational expression. Can you please show me the steps on ...

Algebra Check - What is the simplified form of 3a^4b^-2c^3? a. (81a^4c^3)/(b^2) ...

UOP - help solving 4c divided by 2c minus 4 plus 2c divided by 4c minus 8

Math - how do you factor 2c^2-7c=-5? I know that you have to change it to 2c^2-...

Math - Corey jogs 5km every morning to get ready for a 5km race he is going to ...

maths - (Q1)a+3b+2c=3,2a-b-3c=-8,5a+2b+c=9.solve for a,b&c by matrix method. (a)...

math - Please help! Simplify the rational expression. State any restrictions on ...

Algebra - To simply the expression of 10*(-2c)*3 I need to make sure I ...